Menelanjangi Mens Rea Sendenbu: Analisis Linguistik Forensik terhadap Tindak Tutur Komisif Manipulatif pada Slogan “Nippon Cahaya, Pelindung dan Pemimpin Asia” - Arsyiatin Arroby (Universitas Palan, 2026)
This research deconstructs the manipulative architecture in the propaganda trilogy of the Japanese Army in 1942, namely Nippon Tjahaja Asia, Nippon Pelindoeng Asia, and Nippon Leader Asia, which have often been reduced to mere political euphemisms. With a descriptive-qualitative design, this study integrates Malcolm Coulthard and Alison Johnson's parameter-based Forensic Linguistics as the grand theory, as well as the three-dimensional model of Norman Fairclough's Critical Discourse Analysis (AWK) as an operational analysis instrument. The results of the analysis show that lexical manipulation through the messianic triptych